Use of gas-liquid chromatography as a screening test for toxigenic Clostridium difficile in diarrhoeal stools. Issue 11 (November 1983) - Pepersack, F; Labbe, M; Nonhoff, C; Schoutens, E
Abstract : In order to determine if gas-liquid chromatography (GLC) on concentrated stool extracts could be substituted to cell culture assay for cytotoxicity, we prospectively studied 154 diarrhoeal stools submitted for detection of Clostridium difficile toxin. Isocaproic-positive samples were cultured on egg yolk agar supplemented with cycloserine, cefoxitin and fructose for isolation of C difficile, and on egg yolk agar plus kanamycin for isolation of other clostridium species. Of the 154 samples, 129 were GLC-negative (height of the isocaproic peak less than 1.2 cm) and were toxin-negative. Twenty-five stools yielded isocaproic acid; C difficile isolated from 13 of them, six of which were also toxin-positive. Four other isocaproic-positive samples yielded C bifermentans and C sordellii; all were toxin-negative. These results indicate that a negative GLC is an excellent screening test for excluding C difficile infection; positive results must be checked by toxin testing and culture since they are not necessarily associated with the presence of C difficile or its toxin.